Assessing sick building syndrome in Perpustakaan Sultanah Zanariah (PSZ) Library : towards improving health and productivity in indoor environment / Suleiman Aliyu Shika ... [et al.] - Shika, Suleiman Aliyu; Sapri, Maimunah; Jibril, Jibril D.; Dodo, Mansir; Sivanathan, Sheelah; Dodo, Yakubu Aminu (2012)
Sick Building Syndrome (SBS) is one of the leading negative attributes associated with the Indoor Environmental Quality (IEQ) of buildings. This paper studies the SBS inPerpustakaan Sultanah Zanariah (PSZ) library building in Universiti Teknologi Malaysia (UTM). The five parameters studied are: Indoor Air Quality (temperature; ventilation and humidity); lighting; noise; furniture ergonomics; and Video Display Unit (VDU). The methodology used was more of a triangulation approach. The survey uses questionnaire and several “walkthroughs”. Data analysis was both qualitative (descriptive) and quantitative (statistical). The students constituted the respondents for this study. Perception of students towards the five SBS sources and their accompanying symptoms were studied. Results obtained in the study revealed that PSZ is established to being a sick building, indicating that 21.89% of students suffer from the specific SBS symptoms and 29.67% of students suffer from the general SBS symptoms. Secondly, it was establish from literature that by employing the sustainability concept, significant improvement between the SBS sources (lighting, noise, furniture ergonomics and VDU etc), and students performance satisfaction could be enhanced. This confirms that IEQ variables are significantly positively related to student’s performance, and those extremities of such variables lead to effects in performance satisfaction. The study proposes a strategy that is: feasible, physically practicable and cost effective, to continually improve the IEQ status of PSZ from its present state as perceived by students.